A 3D nanofibrous hydrogel and collagen sponge scaffold promotes locomotor functional recovery, spinal repair, and neuronal regeneration after complete transection of the spinal cord in adult rats. (13th January 2015) - Kaneko, Ai; Matsushita, Akira; Sankai, Yoshiyuki
Abstract: Central nervous system neurons in adult mammals display limited regeneration after injury, and functional recovery is poor following complete transection (>4 mm gap) of a rat spinal cord. A novel combination scaffold composed of 3D nanofibrous hydrogel PuraMatrix and a honeycomb collagen sponge was used to promote spinal repair and locomotor functional recovery following complete transection of the spinal cord in rats. We transplanted this scaffold into 5 mm spinal cord gaps and assessed spinal repair and functional recovery using the Basso, Beattie, and Bresnahan (BBB) locomotor scale. The BBB score of the scaffold-transplanted group was significantly higher than that of the PBS-injected control group from 24 d to 4 months after the operation ( P < 0.001–0.01), reaching 6.0 ± 0.75 (mean ± SEM) in the transplant and 0.70 ± 0.46 in the control groups. Neuronal regeneration and spinal repair were examined histologically using Pan Neuronal Marker, glial fibrillary acidic protein, growth-associated protein 43, and DAPI. The scaffolds were well integrated into the spinal cords, filling the 5 mm gaps with higher numbers of regenerated and migrated neurons, astrocytes, and other cells than in the control group. Mature and immature neurons and astrocytes in the scaffolds became colocalized and aligned longitudinally over >2 mm, suggesting their differentiation, maturation, and function. The spinal cord NF200 content of the transplant group, analyzed by western blot, was more than twice that of the control group, supporting the histological results. Transplantation of this novel scaffold promoted functional recovery, spinal repair, and neuronal regeneration.